2014
DOI: 10.1097/phm.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of the Median Nerve in Carpal Tunnel Syndrome with Diabetic Neuropathy

Abstract: The CSA of the median nerve at the wrist and the wrist/forearm ratio could be useful for diagnosing the comorbidity of CTS with DPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
0
24
2
Order By: Relevance
“…We point out that CSA enlargement in compression sites correlates with a reported susceptibility of diabetic patients for entrapment syndromes . However, it is of interest that our patients lacked relevant symptoms.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…We point out that CSA enlargement in compression sites correlates with a reported susceptibility of diabetic patients for entrapment syndromes . However, it is of interest that our patients lacked relevant symptoms.…”
Section: Discussioncontrasting
confidence: 88%
“…The findings reveal a pronounced increase in CSA of most peripheral nerves in patients with DPN and not only of individual nerves as reported before (for example median nerve in the carpal tunnel and posterior tibial nerve. These morphological abnormalities can be further classified as CSA enlargement in compression sites (carpal tunnel, Guyon canal, ulnar nerve at the elbow, fibular nerve at the fibular head, tibial nerve at the tarsal tunnel) and noncompression sites (median nerve in forearm and fibular nerve in the popliteal fossa).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…These results showing that electrophysiological CTS can be a part of the polyneuropathy in diabetic patients should be interpreted carefully. Kim et al22 ) also found increased CSAs of the median nerve in DPN-only patients compared with those of healthy controls at the wrist. Therefore, ultrasonographic CTS diagnoses are inconsistent with electrophysiological results in patients with DPN.…”
Section: Discussionmentioning
confidence: 85%
“…Kim et al found that all the crosssectional areas (CSA) of the median nerve were larger in DSP patients compared with healthy controls, and the CSA of the median nerve at the wrist revealed no significant differences among DSP patients with and without CTS; however, patients with CTS (with and without DM) had larger CSAs at the wrist and a higher wrist/forearm ratio compared with DSP patients. The cutoff value for the CSA at the wrist that yielded the highest sensitivity and specificity was 11.6 mm [22]. A smaller study found no ultrasound measurement (distal median CSA, wrist-forearm ratio, wrist-forearm difference) reached significance to detect CTS in patients with DSP [17].…”
Section: Electrophysiologic and Ultrasonographic Diagnostic Techniquementioning
confidence: 89%